'Chinese' values in Singapore and Malaysia: an outsider perspective - Soontiens, Werner (Zhongnan University, 2011)
The emergence of China translates in the need to better understand the 'Chinese' population. Chinese ethnicity is strongly represented throughout the Southeast Asian region where, apart from the obvious majority in China, the Chinese ethnic group dominates Singapore and controls the business sector in Malaysia, Indonesia and the Philippines. The Chinese population throughout the region is the 'same' in that all historically originate from mainland China, maintain a strong heritage awareness and promotion of values and tradition. Over time, society values are influenced by different levels of exposure to information and values, especially Western values. The paper reports on the clustering of values amongst Chinese ethnic business students in Singapore and Malaysia. Data collected on 25 values show that, probably not surprisingly, there is a significant overlap between values in Singapore and Malaysia.